Optimization of educational infrastructure projects through an integral risk management plan, Puno case, 2018 - Flores Asencio, Sandra (2022)
As a consequence of the national policy of economic reactivation of the last governments, the aim is to improve the construction sector, however, the stoppage rates of works also increase, the application of a Risk Management Plan being important. The objective was to develop an Integral Plan for the Management of Foreseeable Risks as a proposal to be included in the Technical File, for the planning of the execution of works by direct administration of educational infrastructure projects according to current norms and regulations, aimed at optimizing investment in works. public in the Puno Region. The research method is mixed. The techniques used were documentary analysis, Risk Mapping identification, Risklog risk registry, RBS risk breakdown structure and data assessment through Monte Carlo Simulation. The study population is 22 educational institutions and a case study, the sample is selected and not random. The Integral Risk Management Plan improves the execution of works by direct administration of educational infrastructure, optimizing cost, time, scope and quality, determining an increase of 7.91%, representing a significantly low percentage compared to the increase of 229.16% without the application. of risk management.